2020
DOI: 10.1186/s12877-020-01732-3
|View full text |Cite
|
Sign up to set email alerts
|

Avoidability of drug-induced liver injury (DILI) in an elderly hospital cohort with cases assessed for causality by the updated RUCAM score

Abstract: Background Drug-induced liver injury (DILI) represents an increasing morbidity in the general population, but more so in the elderly cohort of patients. Despite this, the concept of its prevention through prospective analysis has largely remained unexamined. We evaluated the utility of recently validated adverse drug reactions (ADR) avoidability tool in a cohort of elderly patients with DILI. Methods We examined 38 DILI-drug pairs from n=38 patients in a prospective cohort of patients presenting with adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 14 publications
4
28
1
Order By: Relevance
“…The exact agreement proportions between the raters in terms of avoidability was about 80%; which will indicate excellent agreement. Our report is consistent with the agreement proportions reported by the original developers of the tool (9), as well subsequent validation studies (10,14,15). The proportionately higher interrater agreement and avoidability proportions (0.80) reported from our study compared to that by both Louise et al ( 9) and Danjuma et al (10) may be due to the phenotype of the clinical risks the tool (LAAT) was attempting to adjudicate.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The exact agreement proportions between the raters in terms of avoidability was about 80%; which will indicate excellent agreement. Our report is consistent with the agreement proportions reported by the original developers of the tool (9), as well subsequent validation studies (10,14,15). The proportionately higher interrater agreement and avoidability proportions (0.80) reported from our study compared to that by both Louise et al ( 9) and Danjuma et al (10) may be due to the phenotype of the clinical risks the tool (LAAT) was attempting to adjudicate.…”
Section: Discussionsupporting
confidence: 91%
“…The proportionately higher interrater agreement and avoidability proportions (0.80) reported from our study compared to that by both Louise et al ( 9) and Danjuma et al (10) may be due to the phenotype of the clinical risks the tool (LAAT) was attempting to adjudicate. The fact that DRESS syndrome has a distinct cutaneous clinical phenotype may have improved the degree of certainty in both the interrater agreement as well as avoidability determination outcomes compared to that seen with other ADR's (such as drug induced liver injury (15). We do concede that some forms of DRESS syndrome are idiosyncratic in manifestation and may not be amenable to adjuication of potenail avoidability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent Spanish Guidelines for diagnosis, management, treatment, and prevention of DRESS Syndrome made recommendations centered around added predictive values of specific pharmacogenetic makers (such as single nucleotide polymorphisms) encoding implicated drugs 8 . Recently, there has been a rising interest in the determination of the avoidability of adverse drug reactions (ADR) in the general population using novel "avoidability" determination algorithms/tools [9][10][11][12] . One of such tools is the Liverpool adverse drug reaction avoidability tool (LAAT) 9 .…”
mentioning
confidence: 99%
“…In an examination of 38 DILI-drug pairs (using the LAAT) from an elderly cohort of patients, we found that about 32.3% (50/152) of them were rated as “avoidable” (“probably” or “definitely”). 4 We found that the overall median Krippendorf’s κ with the tool was 0.61 (SE = 0.12; CI = 0.36, 0.85), with an interrater correlation coefficient of 0.50 [0.32, 0.65]. The demonstration of >32% of DILI cases as “avoidable” raises the prospect for further examination of these cases (including potentially micafungin cases) with the view to identifying areas for target therapeutic intervention.…”
mentioning
confidence: 99%